Pendampingan Komunitas Karang Taruna dalam Pembuatan Kaligrafi dengan Media Limbah Kaca - Ika Trisnawati Alawiyah; Ahmad Mukhlishin; M. Anwar Nawawi (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2021)
This community assistance program was carried out at the Youth Youth Committee in Tunas Asri Village, Tulang Bawang Tengah District, Tulang Bawang Barat Regency. This assistance is carried out through a calligraphy making program using glass waste media. Glass waste material in Tunas Asri Village is quite adequate, because many people in Tunas Asri Village have glass shops, so that unused glass pieces are quite abundant. The problem is, for the people of Tunas Asri Village, glass waste is considered an unused item, even a lot of glass waste is just thrown away. The focus of writing this article is how to make calligraphy using glass waste in the Karang Taruan community, Tulang Bawang Tengah District, Tulang Bawang Barat Regency?. This assistance uses an Asset Based Community Development (ABCD) theoretical approach, which prioritizes the utilization of assets and potentials that exist around and are owned by the Karang Taruna community, to then be used as materials that empower the community itself. The result of this mentoring program is that glass waste can be used as a medium in making calligraphy art. The resulting products can be of economic value for the assisted communities.